Thymic transcriptome analysis after Newcastle disease virus inoculation in chickens and the influence of host small RNAs on NDV replication - Liangxing Guo (Nature Portfolio, 2021)
Abstract Newcastle disease (ND), caused by virulent Newcastle disease virus (NDV), is a contagious viral disease affecting various birds and poultry worldwide. In this project, differentially expressed (DE) circRNAs, miRNAs and mRNAs were identified by high-throughput RNA sequencing (RNA-Seq) in chicken thymus at 24, 48, 72 or 96 h post LaSota NDV vaccine injection versus pre-inoculation group. The vital terms or pathways enriched by vaccine-influenced genes were tested through KEGG and GO analysis. DE genes implicated in innate immunity were preliminarily screened out through GO, InnateDB and Reactome Pathway databases. The interaction networks of DE innate immune genes were established by STRING website. Considering the high expression of gga-miR-6631-5p across all the four time points, DE circRNAs or mRNAs with the possibility to bind to gga-miR-6631-5p were screened out. Among DE genes that had the probability to interact with gga-miR-6631-5p, 7 genes were found to be related to innate immunity. Furthermore, gga-miR-6631-5p promoted LaSota NDV replication by targeting insulin induced gene 1 (INSIG1) in DF-1 chicken fibroblast cells. Taken together, our data provided the comprehensive information about molecular responses to NDV LaSota vaccine in Chinese Partridge Shank Chickens and elucidated the vital roles of gga-miR-6631-5p/INSIG1 axis in LaSota NDV replication.